Preparing for the Possibility of a North Korean Collapse - Bennett, Bruce W. (RAND Corporation, 2013)
A North Korean government collapse would have serious consequences, including a humanitarian disaster and civil war. The Republic of Korea and the United States can help mitigate the consequences, seeking unification by being prepared to deliver humanitarian aid in the North, stop conflict, demilitarize the North Korean military over time, secure and eliminate North Korean weapons of mass destruction, and manage Chinese intervention.